2021
DOI: 10.1371/journal.pntd.0009586
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control and insecticide resistance status of sand fly vectors worldwide

Abstract: Background Phlebotomine sand flies are prominent vectors of Leishmania parasites that cause leishmaniasis, which comes second to malaria in terms of parasitic causative fatalities globally. In the absence of human vaccines, sand fly chemical-based vector control is a key component of leishmaniasis control efforts. Methods and findings We performed a literature review on the current interventions, primarily, insecticide-based used for sand fly control, as well as the global insecticide resistance (IR) status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 93 publications
0
15
0
2
Order By: Relevance
“…The effective management of leishmaniasis relies on strategies that encompass both vector control as well as accessible chemotherapeutic options to effectively cure the disease [ 6 ]. Since therapy, with obsolete therapeutic drugs, is often marred with issues such as severe side effects, parasitic resistance, and enhanced post-kala-azar dermal leishmaniasis (PKDL) occurrence [ 3 , 7 , 8 , 9 ], repurposing of the drugs, such as AmB, could possibly result in the better clinical management of the disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effective management of leishmaniasis relies on strategies that encompass both vector control as well as accessible chemotherapeutic options to effectively cure the disease [ 6 ]. Since therapy, with obsolete therapeutic drugs, is often marred with issues such as severe side effects, parasitic resistance, and enhanced post-kala-azar dermal leishmaniasis (PKDL) occurrence [ 3 , 7 , 8 , 9 ], repurposing of the drugs, such as AmB, could possibly result in the better clinical management of the disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sand flies, information in the literature on the response profile of wild populations to insecticides around the globe remains seriously limited. However, recent phenotypic data (bioassays) and molecular analyses (e.g., detection of knock-down resistance ( kdr ) mutations L1014F/S in the voltage-gated sodium channel ( VGSC ) gene related to loss of sensitivity to pyrethroids) of dominant sand fly vector species, wild populations originating from countries with the highest leishmaniasis burden in north-eastern Asia and the Middle East, revealed that insecticide resistance in sand flies poses an up-coming and alarming issue [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, potential health and environmental risks are associated with indoor application of pesticides. It has been observed that insecticide-based baits are more effective and ecologically safe in insect-vector control efforts than residual sprays 9 , 10 . Pyrethroid insecticides like lambda-cyhalothrin are among the most popular options for the management of insect-vectors at domestic and commercial scale.…”
Section: Introductionmentioning
confidence: 99%